2014
DOI: 10.2528/pier13110709
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Classifiers for Tumor Detection With an Experimental Time-Domain Breast Screening System

Abstract: Abstract-In this work we examine, for the first time, the use of classification algorithms for earlystage tumor detection with an experimental time-domain microwave breast screening system. The experimental system contains a 16-element antenna array, and testing is done on breast phantoms that mimic breast tissue dielectric properties. We obtain experimental data from multiple breast phantoms with two possible tumor locations. In this work, we investigate a method for detecting the tumors within the breast but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…As was shown in [5] and [8] the dielectric properties of the breast phantom vary over time. In [5], measurements over a period of 7 days demonstrated that the relative permittivity, ε r , at 3 GHz of the healthy breast phantom varied between 5.5 and 19. For "healthy" breast phantoms, the radome is completely filled with the adipose tissue.…”
Section: A System Overview and Data Collectionmentioning
confidence: 92%
See 3 more Smart Citations
“…As was shown in [5] and [8] the dielectric properties of the breast phantom vary over time. In [5], measurements over a period of 7 days demonstrated that the relative permittivity, ε r , at 3 GHz of the healthy breast phantom varied between 5.5 and 19. For "healthy" breast phantoms, the radome is completely filled with the adipose tissue.…”
Section: A System Overview and Data Collectionmentioning
confidence: 92%
“…Similar to [4], [5], we apply both LDA and SVM classifiers, individually, on selected data features that are extracted using Principle Component Analysis (PCA).…”
Section: B Detection Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…The main author has successfully used classification algorithms, such as Linear Discriminant Analysis, Quadratic Discriminant Analysis, Support Vector Machines [1], Spiking Neural Networks [2] and Self-Organising Maps [3], to determine the size and shape of benign and malignant tumour models inside breast models. Other authors have also previously investigated the use of classifiers to aid in determining if a breast model represents a healthy breast or a breast with tumours, in simulation [4] and experimental scenarios [5].…”
Section: Introductionmentioning
confidence: 99%